NATURE AND ENVIRONMENT IN WILLIAM WORDSWORTH'S SELECTED POEMS: AN ECO-CRITICAL APPROACH - Mariwan Hasan; Kosar Muhamad (Association of Social and Educational Innovation, 2020)
In recent years, studying connections between the human being and environment along with nature has been looked at as a topic of significant value for literary researchers. Thus, the emergence of eco-critical approach in the countries, which use English as their first language, holds the first position in this respect. This harmony of the two has been discussed for a while in world literature. This research studies literature review and pinpoints the positive view been presented by looking at eco-criticism. The methods used are textual analysis approach and eco-critical approach. The major points of this study are to investigate the main theme and shed light on it and the way William Wordsworth used his writings to protect the environment from destructions and the writer used eco-criticism or ecology in his works in his time. The environment and ecology in William Wordsworth's poems are the two things which have been dealt with because poems can serve human beings and make them aware of protecting the environment from pollution. This research consists of several essential points about the literature and nature as well as ecology. Besides, the paper presents an introduction about Englandin the nineteenth century, romanticism, and characteristics of romanticism as these are interrelated with eco-criticism.